Ultra-black near-infrared reflection refrigeration optical thin film based on chalcogenide material
By using alternately stacked sulfur-based phase change material absorption layer and dielectric layer structure in the black film, combined with high reflective metal base, the refrigeration effect that takes into account the high absorption of visible broadband and near-infrared ultra-high reflection is achieved, and the problem of temperature rise of black films in the prior art is solved.
Patent Information
- Application Number
- CN202510016768.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-06
- Publication Date
- 2025-04-01
AI Technical Summary
The prior art is difficult to achieve a cooling effect that takes into account the high absorption of visible broadband and low-infrared ultra-high reflection in black films, especially in the lack of effective solutions in temperature rise.
The alternating stacked sulfur-based phase change material absorption layer and dielectric layer structure is used, combined with high reflective metal base, and broadband absorption and near-infrared high reflection are achieved through multi-layer superposition design, and the application of phase change technology in black refrigeration films is explored.
It achieves ultra-high absorption rate in the visible light band (up to 99.5% or more) and ultra-high reflectivity in the near-infrared band (up from 60% to 95%), effectively alleviating the problem of excessive temperature rise caused by absorption of ultra-black films and improving the refrigeration effect.
Smart Images

Figure CN119738905A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of refrigeration optical films, and in particular to an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material. Background Art
[0002] Optical thin film structural color is a color formed based on the diffraction, scattering and interference of light by the microscopic structure of the surface of an object, such as the tail feathers of a male peacock, the wings of a blue butterfly, the stripes of a tropical fish, etc. Compared with chemical color and bioluminescence, this color produced by the interaction between structure and light has the advantages of low loss, insensitivity to the environment, stable color and not easy to fade. Over the years, structural color research has attracted much attention and has been widely used in various fields, such as optical anti-counterfeiting, bionic photonic pigments, optical displays, etc. In the past, most of the structural color research was reflective structural color research, and there was less research on absorption structural color, especially black.
[0003] Black is widely used in the fields of automobiles, construction, etc. However, most black films are fully absorbing films, which heat up quickly and are not friendly to devices in low or high temperature environments. Therefore, it is of great practical significance to produce a black refrigeration optical film. The black refrigeration film is an optical film with broadband full absorption of visible light and high reflection properties in the near infrared.
[0004] To achieve broadband absorbent black film, it is usually necessary to introduce special absorbent materials or combine and superimpose modes that can produce resonant absorption. Common methods include: composite material processing technology, metamaterial absorbent film, and planar absorbent film. Composite material processing technology uses chemical or physical means to structurally transform complex materials so that the composite film has excellent optical effects while also having the excellent properties of each material. Metamaterials are artificially constructed materials with subwavelength sizes and periodic array structures. They have unusual electromagnetic properties that natural materials cannot achieve. They achieve perfect absorption in various frequency ranges by changing the three-dimensional geometric design of the material. However, metamaterial absorbent films and composite material processing technologies often have many materials, complex processes, and high production costs. In contrast, planar absorbent films have broad development prospects.
[0005] Publication No. CN117908173A invented a wide spectrum long-wave infrared metamaterial absorber based on lithium niobate, including a top metal layer, a first dielectric layer, a second dielectric layer, and a bottom metal layer from top to bottom. The two metal layers constitute a resonator to capture incident light, and the dielectric layer improves the absorption rate of the absorber. The resonant wavelength can be changed by the size of the square resonator of the surface metal layer, and the combination of square metal resonators of different wavelengths can broaden the absorption spectrum to achieve broadband absorption. Publication No. CN117586539A proposes a black film manufacturing process based on carbon nanotube technology, by mixing single-walled nanotubes, sodium alkylbenzene sulfonate dispersant, poly (3, 4-ethylenedioxythiophene) styrene sulfonic acid solution and deionized water, filtering to obtain a black retentate, and then washing and drying to obtain a black film. This patent combines the advantages of carbon nanotubes themselves, such as good electrical conductivity, good thermal conductivity, low density, and high strength, into the black film.
[0006] Regarding refrigeration films, the main solutions proposed at this stage include micro-nano processing technology, super surface structure, and one-dimensional layered film technology. However, so far, the invention that can take into account both material color and refrigeration is still immature. Due to the temperature rise problem caused by the absorption of black, it is even more difficult to achieve black film refrigeration.
[0007] Publication No. CN117757151A discloses a refrigeration film based on an in-plane heat-conducting composite layer and a porous array composite layer, wherein the porous array composite layer is located on the in-plane heat-conducting composite layer, and refrigeration is achieved through in-plane heat conduction and high radiation efficiency, but its manufacturing process is relatively complicated; Publication No. CN118082309A discloses a radiative refrigeration film based on enhanced diffuse reflection, including a composite reflection layer and a diffuse reflection layer, taking into account high reflectivity, high diffuse reflection coefficient and high atmospheric window emissivity, but the patent does not involve color requirements in different application scenarios; Publication No. CN110066115A discloses a colored coated glass for enhancing the heat dissipation performance of a solar photovoltaic module and a preparation method thereof, including a glass substrate and a colored coating disposed on the glass substrate, wherein the thermal conductivity of the coating is increased by adding hexagonal boron nitride to the colored coating, and different color pigments are added to develop the appearance color required by the module, thereby preparing a colored coated glass that can enhance the heat dissipation performance of a photovoltaic module, but its radiation efficiency is low and black structural color refrigeration is not involved.
[0008] Phase change materials generally refer to substances with different stable phases. In different states, their physical properties, such as optical constants, electrical conductivity, mass density or thermal conductivity, vary greatly, which is of extraordinary significance for the realization of dynamically tunable structural colors. For example, germanium antimony telluride alloy (GST) and antimony trisulfide (Sb2S3) have two states: crystalline and amorphous. When the crystalline state changes, its refractive index changes significantly, and the optical properties of the layered structure composed of it also change. Common phase change materials can be divided into two types: non-volatile materials and volatile phase change materials. Non-volatile materials have long-term stability and can maintain a stable phase state without energy maintenance after phase change. They are suitable for applications that need to maintain a specific color for a long time. For volatile materials, such as vanadium dioxide (VO2), after the phase change, if there is no subsequent energy input, it will return to the initial state, which is suitable for applications that need to change color frequently.
[0009] Phase change materials have been introduced into the field of optical films, among which chalcogenide materials are the most commonly used. Chalcogenide materials refer to compounds formed by combining S (sulfur), Se (selenium), Te (tellurium) of the VI main group as the main components, with Ge (germanium), P (phosphorus), Sb (antimony), Al (aluminum), Si (silicon) and other elements. They usually have good absorption properties and show great prospects in the field of black films. However, in the past few years, no research team has introduced chalcogenide materials into the design of ultra-black films.
[0010] Publication No. CN115373161A proposes an adaptive dynamic color film, whose structure includes a substrate, a reflective layer, and a vanadium oxide phase change layer. By adding a reflective layer under the VO2 layer, the difference in the phase change optical constants is maximized. By doping VO2 with elements, the phase change temperature range can be from 0-100°. By using VO2 for temperature-controlled phase change, the total color difference of the reflected color at high and low temperatures can be ≥10.0. At different temperatures, this design can automatically present different colors and can be used in actual scenarios of high temperature warning. Publication No. CN116626992A provides a method for phase change color photoresist, whose structure includes a metal layer and a sulfur-based phase change material layer from bottom to top. The metal layer is a semi-transparent reflective layer, and the sulfur-based material is a dielectric layer, which together constitute an asymmetric Fabry-Perot resonant cavity. The color of the photoresist is changed by controlling the thickness and crystallization degree of the phase change layer. Compared with traditional pigments, it uses the principle of optical structural color and has the advantages of anti-oxidation and strong stability.
[0011] In summary, the research on optical structural color films has been relatively sufficient, and the application of film refrigeration technology and sulfur-based materials in the optical field has also made some progress. However, the research on combining black optical structural color films with film refrigeration technology and using the absorption characteristics of sulfur-based materials in the visible light band to further introduce phase change technology into black refrigeration films has not yet appeared. However, black refrigeration coatings are widely demanded in the market, and there has been no good solution to the temperature rise problem of black films. Therefore, it is necessary to adopt new design methods and optimization methods to design ultra-black films that can achieve refrigeration. Summary of the invention
[0012] In view of this, the purpose of the present invention is to propose an ultra-black near-infrared reflective refrigeration optical film based on sulfur-based materials, which can provide an ultra-black reflective refrigeration film structure that takes into account both broadband high absorption of visible light and ultra-high reflection of near-infrared, and further introduce phase change materials to explore the application of phase change technology in black refrigeration films.
[0013] According to one aspect of the present invention, there is provided an ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials, the film comprising alternately stacked chalcogenide phase change material absorption layers and dielectric layers.
[0014] In the above technical solution, it is proposed to use low refractive index materials as dielectric layers, phase change materials (PCM) as absorption layers, and multiple layers are superimposed to achieve broadband absorption, and then use high-reflective metal as the base to further achieve near-infrared high reflection design. This structure ensures ultra-high absorption of the visible light part while also ensuring ultra-high reflection of the near-infrared part, effectively alleviating the problem of excessive temperature rise caused by absorption of ultra-black films. At the same time, since phase change materials such as GSST and GST have a high refractive index and good absorption efficiency in the visible light band, phase change materials are further introduced into the film design to explore the possibility of using sulfur-based materials in ultra-black cooling optical films. Specifically, dielectric materials and phase change materials are used for aliasing. Phase change materials have a high refractive index in the visible light band, while the refractive index of dielectric layer materials is generally low. Different refractive index materials cause light waves to reflect and refract at each layer interface. After the light wave passes through the multi-layer structure, light waves of different wavelengths will have interference effects at different interfaces, thereby enhancing the absorption of some wavelengths of light. Inserting a dielectric layer between the absorption layers can also effectively alleviate the interface reflection introduced by the high refractive index of the phase change layer, further reducing the reflectivity. At the same time, in this multi-layer design, in order to increase absorption, a material layer with strong absorption characteristics is generally added. During the process of multiple reflections and refractions, the light waves are further consumed in these absorption layers, thereby improving the absorption efficiency of the entire film structure. During the research process, it was found that sulfur-based materials such as GST and GSST generally have the characteristics of a high extinction coefficient and a high refractive index in the visible light band. It can be used to replace the high refractive index layer (such as TiO2 and other materials) in the traditional high and low refractive index superposition structure, so that sulfur-based phase change materials can be used in the film design.
[0015] In some embodiments, the film is composed of a metal layer, and a chalcogenide phase change material absorption layer and a dielectric layer alternately stacked on the metal layer.
[0016] In the above technical solution, under the aforementioned structural design, the ultra-high absorption of the visible light band can reach an absorption rate of more than 99%, but there is still room for improvement in the transmittance and reflection of the near-infrared band. Therefore, it is proposed to add a layer of high-reflection metal to the bottom layer, which can not only reduce the transmittance of the entire film structure and further increase the absorption rate of the visible light part to more than 99.5%, but also further increase the reflectivity of the near-infrared band from about 60% to 95%, so that the thin film reflection cooling effect is further improved.
[0017] In some embodiments, the material of the metal layer includes: aluminum, silver, and gold.
[0018] In the above technical solution, the bottom metal can be flexibly replaced: this flexibility allows the selection of the most suitable metal in different application scenarios, such as aluminum, silver, gold, etc., to achieve specific functional requirements. By selecting metal materials with different electrical and thermal conductivities, the overall performance of the film can be further optimized to achieve specific functional requirements, such as higher thermal conductivity or stronger mechanical support.
[0019] In some embodiments, the sulfur-based phase change material includes: GSST, SS, VO2, GST.
[0020] In some embodiments, the material of the dielectric layer includes: SiO2, MgF2.
[0021] In the above technical solution, the dielectric layer material and the phase change layer material are replaceable: the phase change material may include GSST, GST, VO2, etc., and the dielectric layer material may be replaced by materials with similar optical properties such as MgF2 and SiO2. This compatibility expands the range of material selection and provides more space for design and optimization.
[0022] In some embodiments, the Fresnel amplitude reflection coefficient and transmission coefficient of the absorption layer are calculated by the following formula:
[0023]
[0024] Wherein, r is the Fresnel amplitude reflection coefficient of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, μ1 and ν1 are functions of the incident angle and the extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and is the amplitude and phase of the amplitude reflection coefficient on the second interface, τ1 and β1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface, ρ and is the amplitude and phase of the amplitude reflection coefficient of the absorption layer, τ and γ are the amplitude and phase of the amplitude transmission coefficient of the absorption layer, and β is the phase thickness.
[0025] In the above technical solution, in order to better introduce the phase change material into the thin film design, the above formula is derived to calculate the Fresnel amplitude reflection coefficient and transmission coefficient of the sulphur-based phase change material absorption layer.
[0026] In some embodiments, the reflectivity and reflection phase shift of the absorption layer are calculated by the following formula:
[0027]
[0028] Wherein, R is the reflectivity of the absorption layer, is the reflection phase shift of the absorption layer, r is the Fresnel amplitude reflection coefficient of the absorption layer, μ1 and ν1 are functions of the incident angle and the extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface, and β is the phase thickness.
[0029] In the above technical solution, in order to better introduce the phase change material into the thin film design, the above formula is derived based on the Fresnel amplitude reflection coefficient and the transmission coefficient to calculate the reflectivity and reflection phase shift of the sulfur-based phase change material absorption layer.
[0030] In some embodiments, the transmittance and transmission phase shift of the absorption layer are calculated by the following formula:
[0031]
[0032] Wherein, T is the transmittance of the absorption layer, γ is the transmission phase shift of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, n2 and n0 are the refractive indices of the substrate medium and the incident medium respectively, is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, 1 and 1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, 2 and 2 are the amplitude and phase of the amplitude transmission coefficient on the second interface, ρ1 is the amplitude of the amplitude reflection coefficient on the first interface, and ρ2 is the amplitude of the amplitude reflection coefficient on the second interface.
[0033] In the above technical solution, in order to better introduce the phase change material into the thin film design, the above formula is derived based on the Fresnel amplitude reflection coefficient and the transmission coefficient to calculate the transmittance and transmission phase shift of the sulfur-based phase change material absorption layer.
[0034] According to another aspect of the present invention, a method for preparing an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material is provided, and the method is used for the above-mentioned ultra-black near-infrared reflective cooling optical film based on a chalcogenide material. The method comprises: using a deposition method and / or a coating method to prepare an alternately stacked chalcogenide phase change material absorption layer and a dielectric layer.
[0035] In the above technical solution, the multi-layer stacking structure facilitates the use of common deposition and coating techniques, such as sputtering, chemical vapor deposition (CVD), etc., which simplifies the production process and improves manufacturing efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0037] Figure 1 This is a basic structural diagram of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0038] Figure 2 It is a schematic diagram of the propagation of the electric field at the interface of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0039] Figure 3 This is a schematic diagram of light passing through a single-layer film in an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0040] Figure 4 It is a schematic diagram of solving the characteristic matrix of a multilayer film according to an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0041] Figure 5 Schematic diagram of a single-layer absorption film of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0042] Figure 6 Schematic diagram of a single-layer absorption film of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0043] Figure 7 This is a schematic diagram of the color change of an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material according to an embodiment of the present invention at an incident angle of 0 to 45 degrees;
[0044] Figure 8 This is a schematic diagram of a color change caused by amorphous-crystalline transition of an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material according to an embodiment of the present invention;
[0045] Fig. 9 This is a spectrum diagram of Example 1 of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0046] Fig.10 This is a spectrum diagram of Example 2 of an embodiment of an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material of the present invention;
[0047] Fig.11This is a spectrum diagram of Example 3 of an embodiment of an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material of the present invention;
[0048] Fig.12 This is a spectrum diagram of Example 4 of an embodiment of an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material of the present invention;
[0049] Fig.13 This is a spectrum diagram of Example 5 of an embodiment of an ultra-black near-infrared reflective cooling optical film based on a chalcogenide material of the present invention;
[0050] Fig.14 This is a spectrum diagram of Example 6 of an embodiment of an ultra-black near-infrared reflective cooling optical film based on a sulfur-based material of the present invention. DETAILED DESCRIPTION
[0051] The present invention will be further described in detail below in conjunction with the accompanying drawings and examples. It is particularly noted that the following examples are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Similarly, the following examples are only partial embodiments of the present invention rather than all embodiments, and all other embodiments obtained by those of ordinary skill in the art without creative work are within the scope of protection of the present invention.
[0052] The present invention provides an ultra-black near-infrared reflective refrigeration optical film based on sulfur-based materials, which can provide an ultra-black reflective refrigeration film structure that takes into account both broadband high absorption of visible light and ultra-high reflection of near-infrared, and further introduces phase change materials to explore the application of phase change technology in black refrigeration films.
[0053] Embodiment 1
[0054] See also Figure 1, an ultra-black near-infrared reflective cooling optical film based on chalcogenide materials, which consists of alternately stacked chalcogenide phase change material absorption layers and dielectric layers. It is proposed to use low-refractive index materials as dielectric layers and phase change materials (PCM) as absorption layers, and to achieve broadband absorption by multi-layer superposition, and then use high-reflective metal as the base to further achieve near-infrared high reflection design. This structure ensures ultra-high absorption of the visible light part while also ensuring ultra-high reflection of the near-infrared part, effectively alleviating the problem of excessive temperature rise caused by absorption of ultra-black films. At the same time, since phase change materials such as GSST and GST have a high refractive index and good absorption efficiency in the visible light band, phase change materials are further introduced into the film design to explore the possibility of using chalcogenide materials in ultra-black cooling optical films. Specifically, dielectric materials and phase change materials are used for aliasing. Phase change materials have a high refractive index in the visible light band, while the refractive index of dielectric layer materials is generally low. Different refractive index materials cause light waves to reflect and refract at each layer interface. After the light waves pass through the multi-layer structure, light waves of different wavelengths will interfere with each other at different interfaces, thereby enhancing the absorption of some wavelengths of light. Inserting a dielectric layer between the absorption layers can also effectively alleviate the interface reflection introduced by the high refractive index of the phase change layer, further reducing the reflectivity. At the same time, in this multi-layer design, in order to increase absorption, a material layer with strong absorption characteristics is generally added. During the process of multiple reflections and refractions, the light waves are further consumed on these absorption layers, thereby improving the absorption efficiency of the entire film structure. During the research process, it was found that sulfur-based materials such as GST and GSST generally have the characteristics of a high extinction coefficient and a high refractive index in the visible light band. It can be used to replace the high refractive index layer (such as TiO2 and other materials) in the traditional high and low refractive index superposition structure, so that sulfur-based phase change materials can be used in the film design.
[0055] In this embodiment, the film is composed of a metal layer, and a sulfur phase change material absorption layer and a dielectric layer alternately stacked on the metal layer. Under the aforementioned structural design, the ultra-high absorption of the visible light band can reach an absorption rate of more than 99%, but there is still room for improvement in the transmittance and the reflection part of the near-infrared band. Therefore, it is proposed to add a layer of highly reflective metal to the bottom layer, which can not only reduce the transmittance of the entire film structure and further increase the absorption rate of the visible light part to more than 99.5%, but also further increase the reflectivity of the near-infrared band from about 60% to 95%, so that the thin film reflection cooling effect is further improved.
[0056] In this embodiment, the material of the metal layer includes: aluminum, silver, and gold. The bottom metal can be flexibly replaced: This flexibility allows the selection of the most suitable metal, such as aluminum, silver, gold, etc., in different application scenarios to achieve specific functional requirements. By selecting metal materials with different electrical conductivity and thermal conductivity, the overall performance of the film can be further optimized to achieve specific functional requirements, such as higher thermal conductivity or stronger mechanical support.
[0057] In this embodiment, the chalcogenide phase change material includes: GSST, SS, VO2, GST. The material of the dielectric layer includes: SiO2, MgF2. The dielectric layer material and the phase change layer material are replaceable: the phase change material may include GSST, GST, VO2, etc., and the dielectric layer material may be replaced with materials with similar optical properties such as MgF2, SiO2, etc. This compatibility expands the range of material selection and provides more space for design and optimization.
[0058] In this embodiment, the Fresnel amplitude reflection coefficient and transmission coefficient of the absorption layer are calculated by the following formula:
[0059]
[0060] Wherein, r is the Fresnel amplitude reflection coefficient of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, ρ and is the amplitude and phase of the amplitude reflection coefficient of the absorption layer, τ and γ are the amplitude and phase of the amplitude transmission coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface.
[0061] In this embodiment, the reflectivity and reflection phase shift of the absorption layer are calculated by the following formula:
[0062]
[0063] Wherein, R is the reflectivity of the absorption layer, is the reflection phase shift of the absorption layer, r is the Fresnel amplitude reflection coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface.
[0064] In this embodiment, the transmittance and transmission phase shift of the absorption layer are calculated by the following formula:
[0065]
[0066] Wherein, T is the transmittance of the absorption layer, γ is the transmission phase shift of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, μ1 and ν1 are functions of the incident angle and the extinction coefficient, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface, n2 and n0 are the refractive indices of the base medium and the incident medium respectively, ρ1 is the amplitude of the amplitude reflection coefficient on the first interface, ρ2 is the amplitude of the amplitude reflection coefficient on the second interface, and β is the phase thickness.
[0067] In order to better explain this embodiment, the following will further explain:
[0068] See also Figure 1 The first N layers are alternately stacked by dielectric layers and PCM layers, and the bottom layer is made of metal, which can be simply described as (DP) ^n -M, D is a dielectric layer (Dielectric), P is a phase change layer (PCM), and M is a metal (Metal). The first N layers use dielectric materials and phase change materials for overlapping. Phase change materials have a higher refractive index in the visible light band, while the refractive index of dielectric layer materials is generally low. Different refractive index materials cause light waves to reflect and refract at each layer interface. After the light wave passes through the multi-layer structure, light waves of different wavelengths will have interference effects at different interfaces, thereby enhancing the absorption of some wavelengths of light. Inserting a dielectric layer between the absorption layers can also effectively alleviate the interface reflection introduced by the high refractive index of the phase change layer, further reducing the reflectivity. At the same time, in this multi-layer design, in order to increase absorption, a material layer with strong absorption characteristics is generally added. During the process of multiple reflections and refractions, the light wave is further consumed in these absorption layers, thereby improving the absorption efficiency of the entire film structure. During the research process, it was found that sulfur-based materials such as GST and GSST generally have the characteristics of a high extinction coefficient and a high refractive index in the visible light band. It can be used to replace the high refractive index layer (such as TiO2 and other materials) in the traditional high and low refractive index superposition structure, so that the sulfur-based phase change material can be used in the film design. By further studying the specific phase change conditions, a wider range of application scenarios may be discovered.
[0069] The specific analysis method is further given below:
[0070] Light waves belong to electromagnetic waves, so Maxwell's equations are the most effective way to describe the transmission process of light in thin films. By solving Maxwell's equations, we can get that at any point in the transmission medium, the propagation direction is always vertical, and there is a ratio between the values:
[0071]
[0072] Where Y is called optical admittance; N is the complex refractive index of the medium, and N = n-ik, n is the refractive index of the medium, k is the extinction coefficient of the medium; ε0 and μ0 are the dielectric constant and magnetic permeability in vacuum respectively; μ of general optical materials at optical frequencies is r are all close to 1, so the above formula can be rewritten as It is the free space admittance, and its value in the International System of Units is 1 / 377 Siemens, so the complex refractive index of the medium is usually used to represent its optical admittance. The optical admittance of a medium describes the characteristics of the medium, revealing the changes in the characteristics of the light reaching its surface and the light transmitted inside it. It is a very useful parameter for characterizing the characteristics of optical materials. The same material has different admittances for light of different wavelengths, which is called the dispersion of the material.
[0073] As we all know, light will reflect and refract at the interface between two different media. Part of the light is reflected back to the original medium, while the other part enters the new medium and propagates. The law of reflection states that when light is reflected at the interface between two media, the angle of incidence is equal to the angle of reflection. Snell's refraction law N0sinθ0=N1sinθ1, where N0 and N1 are the refractive indices of the two materials, θ0 and θ1 are the angle of incidence and the angle of emission, respectively, which gives the change in propagation direction of light when it is refracted. From the perspective of light energy, using the electromagnetic wave theory of Maxwell's equations to explain the reflection and refraction phenomena can obtain the energy relationship between the reflection and refraction processes, which is the famous Fresnel reflection coefficient and transmission coefficient formula. When light is incident vertically and both media are non-absorbing media, use the following formula: Figure 2 The symbol convention shown is:
[0074] Amplitude reflection coefficient:
[0075]
[0076] Amplitude transmission coefficient:
[0077]
[0078] Intensity Reflectivity:
[0079]
[0080] Intensity Transmittance
[0081]
[0082] When the light is incident at an angle, the situation becomes slightly more complicated, but the above formula still applies, as long as the admittance of the medium is replaced by the equivalent admittance of S-polarized and P-polarized light:
[0083]
[0084] The propagation process of light in multilayer films is very complicated, and it is very complicated to directly calculate using the characteristics of beam interference. Therefore, the characteristic admittance matrix method based on the solution of Maxwell's equations is used for calculation, such as Figure 3 As shown, for a single-layer film, using the boundary conditions at the interface and the propagation theory of electromagnetic waves, the following relationship can be derived:
[0085]
[0086] in, It is called phase thickness.
[0087]
[0088] Formula (6) is called the characteristic matrix of the film, which contains all the useful parameters of the film. Matrix [BC] T It is defined as the combined characteristic matrix of the film and the substrate, so the combined admittance Y = C / B, and the combined amplitude reflection coefficient is:
[0089]
[0090] The combined energy reflectivity is:
[0091]
[0092] When the light is incident at an angle, the above formula is also applicable. In this case, we only need to substitute the equivalent admittance of the corresponding P-component and S-component into the above formula:
[0093]
[0094] By extending the above discussion on single-layer membranes to multilayer membranes, we can obtain the calculation of the combined characteristic matrix of any number of multilayer membrane systems, such as Figure 4 shown.
[0095] The characteristic matrix of the entire film system is:
[0096]
[0097] in
[0098] The previous section mainly introduces some methods for calculating the characteristics of dielectric thin films (non-absorption). The calculation of the characteristics of a film stack containing an absorbing film is more complicated than that of a dielectric thin film. In theory, as long as the refractive index of the absorbing film is replaced by the complex refractive index n-ik, the previous analysis method can also be used to analyze the absorbing thin film system.
[0099] Consider a thin film system with a single absorbing film between the incident medium and the substrate, such as Figure 5 As shown, its refractive index is a complex number N1=n1-ik1, so the cosine of the refraction angle cosθ1 and the phase thickness δ1 of the absorption film are both complex numbers containing real and imaginary parts.
[0100] In order to simplify the analytical expressions of the reflection and transmission characteristics of the single-layer absorption film, let N1θ1=μ1+V1, where μ1 and ν1 are real numbers, then
[0101] (μ1+iυ1) 2 =N1 2 (1-sin 2 θ1) (11)
[0102] According to the law of refraction N1sinθ1=N0sinθ0, we can get:
[0103] (μ1+iυ1) 2 =N1 2 -N0 2 sin 2 θ0 (12)
[0104] The real part and the imaginary part are equal, so
[0105] μ1 2 -υ1 2 =n1 2 -k1 2 -N0 2 sin 2 θ0 (13)
[0106] μ1υ1=-n1k1 (14)
[0107] From the above two equations, we can solve:
[0108]
[0109] Therefore, μ1 and ν1 are functions of the incident angle θ0 and the extinction coefficient k1. For the S-component, n1 = N1cosθ1 = μ1 + ν1. According to the above-mentioned formula for the Fresnel amplitude reflection coefficient of the S-component, we can obtain:
[0110] From the above formula, we can get the amplitude ρ1 and phase of the amplitude reflection coefficient on the first interface The expression is:
[0111]
[0112] The Fresnel amplitude transmission coefficient formula can also be used to obtain:
[0113]
[0114] And then:
[0115]
[0116] Using the same method, combined with the refraction law N1sinθ1=N2sinθ2, we can continue to derive the expressions of the amplitude reflection coefficient and amplitude transmission coefficient on the second interface:
[0117]
[0118] For the P-component, n1=N1 / cosθ1=μ1+v1. The same method can be used to obtain the expressions of the amplitude transmission coefficient and the amplitude reflection coefficient on the two interfaces.
[0119] Amplitude reflection coefficient of the first interface:
[0120]
[0121] but
[0122]
[0123]
[0124] Amplitude transmission coefficient of the first interface:
[0125]
[0126] but:
[0127]
[0128] Similarly, the expression of the relationship between reflection and transmission of the second interface can be obtained,
[0129] reflection:
[0130]
[0131] transmission:
[0132]
[0133] Combining the above derivations, we can write the analytical expressions of the amplitude reflection coefficient and amplitude transmission coefficient of a single-layer absorbing film, let:
[0134]
[0135] So the Fresnel amplitude reflection coefficient and transmission coefficient can be rewritten as:
[0136]
[0137] Wherein, r is the Fresnel amplitude reflection coefficient of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, ρ and is the amplitude and phase of the amplitude reflection coefficient of the absorption layer, τ and γ are the amplitude and phase of the amplitude transmission coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface.
[0138] The reflectivity R and reflection phase shift can be obtained from the reflection coefficient
[0139]
[0140] Wherein, R is the reflectivity of the absorption layer, is the reflection phase shift of the absorption layer, r is the Fresnel amplitude reflection coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface.
[0141] The transmittance T and transmission phase shift γ can also be obtained from the transmission coefficient:
[0142]
[0143] In the formula, T is the transmittance of the absorption layer, γ is the transmission phase shift of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, n2 and n0 are the refractive indices of the base medium and the incident medium respectively, β is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface, ρ1 is the amplitude of the amplitude reflection coefficient on the first interface, and ρ2 is the amplitude of the amplitude reflection coefficient on the second interface.
[0144] Using the previous formula analysis, we can get: 1) The reflectivity increases with the thickness of the absorption film, and the transmittance decreases with the thickness of the absorption film, and eventually tends to be constant; 2) As the extinction coefficient increases, the reflectivity is higher and the transmittance is lower, and the characteristics of the absorption film deviate more from the dielectric film; 3) The refractive index n has a greater impact on the reflectivity, while the extinction coefficient k has a greater impact on the transmittance.
[0145] Based on the above analysis, under the structural design of the first N layers, ultra-high absorption in the visible light band can reach an absorption rate of more than 99%, but there is still room for improvement in the transmittance and reflection of the near-infrared band.
[0146] Therefore, it is proposed to add a layer of highly reflective metal to the bottom layer, which can not only reduce the transmittance of the entire film structure and further increase the absorption rate of the visible light part to more than 99.5%, but also further increase the reflectivity of the near-infrared band from about 60% to 95%, thereby further enhancing the thin film reflective cooling effect.
[0147] One of the benefits of the present invention is:
[0148] The invention realizes the ultra-black film with low-angle effect of near-infrared high reflection, and has the following functional advantages:
[0149] 1. Ultra-wideband absorption in the visible light band (wavelength: 380-760nm), with an average absorption rate of up to 99.6% and a peak absorption rate of up to 99.8%, can achieve ultra-black structural color, and by adjusting the thickness of some layers, the blackness can be adjusted to meet the needs of various scenarios. For example, for automotive coatings, bright black is generally used, while ultra-black materials are required in scenarios such as high-precision optical instruments (such as space telescopes and lithography machines).
[0150] 2. Achieve high reflectivity in near-infrared wavelengths (wavelength: 800nm-2500nm), with an average reflectivity of up to 90% and a peak reflectivity of up to 92%, such as Figure 6 As shown in the figure, in the solar infrared spectrum, energy is mostly accumulated in the near-infrared band. Compared with the full-band absorption of common black materials on the market, this film structure can further achieve full reflection of energy in the near-infrared band, which can reduce the heating efficiency in scenes such as sun exposure and achieve reflective cooling.
[0151] 3. Low angle effect: Figure 7 As shown, the structure involved in this invention is insensitive to the incident angle between 0° and 45°. Compared with the problem of a traditional high-reflection film with a sharp drop in reflectivity at large incident angles, this structure has low spectral drift.
[0152] The present invention is beneficial in two aspects:
[0153] By introducing sulfur-based materials with phase change properties, structural color regulation can be achieved in different phases.
[0154] Since non-volatile PCM materials have reversible phase changes under fixed conditions, low power consumption, and stable state, they are excellent choices for producing tunable thin film structural colors. In the present invention, phase change sulfur-based materials are introduced, which are ultra-black in the amorphous state and have a visible light absorption rate of more than 99%. Figure 8 As shown in the figure, the structure is (SiO2-GST)^3-Al. The color change can be achieved by changing the GST from an amorphous state to a crystalline state. The phase change is high-speed and adjustable, which broadens the application of dynamically tunable structural colors.
[0155] The present invention is beneficial in three aspects:
[0156] This design has a simple structure, few types of materials and is easy to process. The first six layers are made of two materials alternately stacked, and the seventh layer is metal. The simple multi-layer stacking structure facilitates the use of common deposition and coating technologies, such as sputtering and chemical vapor deposition (CVD), which simplifies the production process and improves manufacturing efficiency.
[0157] The fourth benefit of the present invention is:
[0158] This design structure is universal. Within this structural framework, ultra-black passive cooling films can be achieved by selecting materials as needed and optimizing the film thickness in a targeted manner:
[0159] 1. The bottom metal can be flexibly replaced: This flexibility allows the selection of the most suitable metal in different application scenarios, such as aluminum, silver, gold, etc., to achieve specific functional requirements. By selecting metal materials with different electrical and thermal conductivity, the overall performance of the film can be further optimized to achieve specific functional requirements, such as higher thermal conductivity or stronger mechanical support.
[0160] 2. The dielectric layer material and phase change layer material are replaceable: the phase change material can include GSST, GST, VO2, etc., and the dielectric layer material can be replaced by materials with similar optical properties such as MgF2 and SiO2. This compatibility expands the range of material selection and provides more space for design and optimization.
[0161] Six specific examples are shown below:
[0162] Example 1: (SiO2-GSST(A))^2-Al
[0163] The total number of layers of the film is 5, of which GSST (A) is the phase change layer and also serves as the absorption layer, SiO2 is the dielectric layer, and Al is the metal substrate. The thickness of each film layer is given in Table 1. The spectrum is shown in Fig. 9As shown in the figure, the film structure achieves broadband absorption in the visible light band, with an absorption rate of up to 99%, high reflection in the near-infrared band, and an average reflectivity of up to 80%, which can achieve ultra-black near-infrared reflective cooling film. This example shows that when the number of layers is low, some indicators decrease, but not significantly, which further proves the practicality of the structure.
[0164] Table 1 Example 1 Parameters
[0165] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Material <![CDATA[SiO2]]> GSST(A) <![CDATA[SiO2]]> GSST(A) Al Thickness / nm 56.61 5.58 33.87 109.95 152.65
[0166] Example 2: (SiO2-GSST(A))^3-Al
[0167] The total number of layers of the ultra-black film is 7, of which GSST (A) is the phase change layer and also serves as the absorption layer, SiO2 is the dielectric layer, and Al is the metal substrate. The thickness of each film layer is given in Table 2. Its spectrum is shown in Fig.10 As shown in the figure, it can be seen that the film structure achieves broadband absorption in the visible light band with an absorption rate of up to 99.7%, and is highly reflective in the near-infrared band with an average reflectivity of up to 96%, which can realize an ultra-black near-infrared reflective refrigeration film.
[0168] Table 2 Example 2 Parameters
[0169] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Layer6 Layer7 Material <![CDATA[SiO2]]> GSST(A) <![CDATA[SiO2]]> GSST(A) <![CDATA[SiO2]]> GSST(A) Al Thickness / nm 60.3 6.2 30.0 61.3 165.0 24.2 151.9
[0170] Example 3: (SiO2-GSST(A))^3-Ag
[0171] The total number of layers of the ultra-black film is 7, of which GSST (A) is the phase change layer and also serves as the absorption layer, SiO2 is the dielectric layer, and Ag is the metal substrate. The thickness of each film layer is given in Table 3. The spectrum is shown in Fig.11 As shown in the figure, it can be seen that the film structure achieves broadband absorption in the visible light band with an absorption rate of up to 99%, and is highly reflective in the near-infrared band with an average reflectivity of up to 96%, which can realize an ultra-black near-infrared reflective cooling film.
[0172] Table 3 Example 3 Parameters
[0173] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Layer6 Layer7 Material <![CDATA[SiO2]]> GSST(A) <![CDATA[SiO2]]> GSST(A) <![CDATA[SiO2]]> GSST(A) Ag Thickness / nm 58 6 30 65 119 24 630
[0174] Example 4: (MgF2-GSST(A))^3-Al
[0175] The total number of layers of the ultra-black film is 7, of which GSST (A) is the phase change layer and also serves as the absorption layer, MgF2 is the dielectric layer, and Al is the metal substrate. The thickness of each film layer is given in Table 4. The spectrum is shown in Fig.12As shown in the figure, it can be seen that the film structure achieves broadband absorption in the visible light band with an absorption rate of up to 99%, high reflection in the near-infrared band, and an average reflectivity of up to 95%, which can realize an ultra-black near-infrared reflective cooling film.
[0176] Table 4 Example 4 Parameters
[0177] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Layer6 Layer7 Material <![CDATA[MgF2]]> GSST(A) <![CDATA[MgF2]]> GSST(A) <![CDATA[MgF2]]> GSST(A) Al Thickness / nm 62.6 5.3 38.8 71.3 186.2 26.3 168.3
[0178] Example 5: (SiO2-SS)^3-Ag
[0179] The total number of layers of the ultra-black film is 7, of which SS is the phase change layer and also serves as the absorption layer, SiO2 is the dielectric layer, and Al is the metal substrate. The thickness of each film layer is given in Table 5. The spectrum is shown in Fig.13 As shown in the figure, it can be seen that the film structure achieves broadband absorption in the visible light band with an absorption rate of up to 96%, high reflection in the near-infrared band, and an average reflectivity of up to 93%, which can realize a black near-infrared reflective cooling film.
[0180] Table 5 Example 5 Parameters
[0181] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Layer6 Layer7 Material <![CDATA[SiO2]]> SS <![CDATA[SIO2]]> SS <![CDATA[SiO2]]> SS Ag Thickness / nm 49.8 3.6 34.6 74.8 107.1 32.3 292.4
[0182] Example 6: (SiO2-VO2)^3-Al
[0183] The total number of layers of the ultra-black film is 7, of which VO2 is the phase change layer and also serves as the absorption layer, SiO2 is the dielectric layer, and Al is the metal substrate. The thickness of each film layer is given in Table 6. The spectrum is shown in Fig.14 As shown in the figure, it can be seen that the film structure achieves broadband absorption in the visible light band with an absorption rate of up to 95%, high reflection in the near-infrared band, and an average reflectivity of up to 80%, which can realize a black near-infrared reflective cooling film.
[0184] Table 6 Example 6 Parameters
[0185] Layer Layer1 Layer2 Layer3 Layer4 Layer5 Layer6 Layer7 Material <![CDATA[SiO2]]> <![CDATA[VO2]]> <![CDATA[SIO2]]> <![CDATA[VO2]]> <![CDATA[SiO2]]> <![CDATA[VO2]]> Al Thickness / nm 62.3 6.2 16.7 80.3 163.4 34.6 1229.7
[0186] The above descriptions are only some embodiments of the present invention, and are not intended to limit the protection scope of the present invention. Any equivalent device or equivalent process transformation made using the contents of the present invention specification and drawings, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. An ultra-black near-infrared reflective cooling optical film based on chalcogenide materials, characterized in that: The film consists of alternately stacked sulfur-based phase change material absorption layers and dielectric layers.
2. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 1, characterized in that: The film consists of a metal layer, and a sulfur-based phase-change material absorption layer and a dielectric layer alternately stacked on the metal layer.
3. An ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material as claimed in claim 1 or 2, characterized in that: The sulfur-based phase change materials include: GSST, SS, VO2, and GST.
4. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 1 or 2, characterized in that: The materials of the dielectric layer include: SiO2 and MgF2.
5. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 2, characterized in that: The materials of the metal layer include: aluminum, silver, and gold.
6. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 1, characterized in that: The Fresnel amplitude reflection coefficient and transmission coefficient of the absorption layer are calculated by the following formula: Wherein, r is the Fresnel amplitude reflection coefficient of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, ρ and is the amplitude and phase of the amplitude reflection coefficient of the absorption layer, τ and γ are the amplitude and phase of the amplitude transmission coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface.
7. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 6, characterized in that: The reflectivity and reflection phase shift of the absorption layer are calculated by the following formula: Wherein, R is the reflectivity of the absorption layer, is the reflection phase shift of the absorption layer, r is the Fresnel amplitude reflection coefficient of the absorption layer, β is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, ρ1 and are the amplitude and phase of the amplitude reflection coefficient on the first interface, ρ2 and are the amplitude and phase of the amplitude reflection coefficient on the second interface.
8. The ultra-black near-infrared reflective refrigeration optical film based on chalcogenide materials according to claim 6, characterized in that: The transmittance and transmission phase shift of the absorption layer are calculated by the following formula: In the formula, T is the transmittance of the absorption layer, γ is the transmission phase shift of the absorption layer, t is the Fresnel amplitude transmission coefficient of the absorption layer, n2 and n0 are the refractive indices of the base medium and the incident medium respectively, β is the phase thickness, μ1 and ν1 are functions of the incident angle and the extinction coefficient, τ1 and γ1 are the amplitude and phase of the amplitude transmission coefficient on the first interface, τ2 and γ2 are the amplitude and phase of the amplitude transmission coefficient on the second interface, ρ1 is the amplitude of the amplitude reflection coefficient on the first interface, and ρ2 is the amplitude of the amplitude reflection coefficient on the second interface.
9. A method for preparing an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material, characterized in that: The method is used to prepare an ultra-black near-infrared reflective refrigeration optical film based on a chalcogenide material as described in any one of claims 1 to 8; the method comprises: preparing alternately stacked chalcogenide phase change material absorption layers and dielectric layers by a deposition method and / or a coating method.
Citation Information
Patent Citations
Colorful coating glass capable of enhancing cooling performance of solar photovoltaic assembly and preparation method
CN110066115A
Self-adaptive dynamic color film as well as preparation method and application thereof
CN115373161A
Phase change color photoresist and preparation method of pixelated color filter thereof
CN116626992A
Preparation method of high-conductivity self-supporting carbon nanotube composite film
CN117586539A
Uniform heat radiation refrigeration film and preparation method thereof
CN117757151A